Incidental findings of root canal anatomy of first and second molars with the eyes of cone beam computed tomography - Anjali Gupta; Nandika Babele; Tushar Phulambrikar; Siddharth Kumar Singh (Wolters Kluwer Medknow Publications, 2015)
Cone beam computed tomography (CBCT) is an imaging modality that enables to visualize the dental structures in three dimensions, which is beyond the scope of conventional radiographs being used. A thorough understanding of the complexity of dental structures is necessary to devise a proper treatment plan and assure the best prognosis. This is made possible by the use of CBCT in all the specialties of dentistry. This case report presents the incidental findings as visualized on CBCT, viz., C-shaped canal and a molar with six root canals, which may pose a problem while being treated endodontically. Thus, the use of CBCT while treating them ensured the success of treatment and its prognosis.